Abstract 216: Endovascular Thrombectomy +/‐ Thrombolytics In Patients With Cocaine‐Related Acute Ischemic Stroke - Sachin A. Kothari; Harsh Desai; Rami Z. Morsi; Julian Carrion‐Penagos; Matthew Smith; Elisheva Coleman; Tareq Kass‐Hout; James Brorson; Shyam Prabhakaran; Scott Mendelson (Stroke: Vascular and Interventional Neurology)
Introduction The safety of thrombolytic therapy in patients with cocaine‐related acute ischemic strokes (AIS) has been investigated, but the safety of endovascular thrombectomy in cocaine‐related AIS remains unknown (1‐2). Here, we report preliminary descriptive data on endovascular thrombectomy with or without thrombolytics performed in cocaine‐related ischemic strokes at our institution. Methods A retrospective chart review was performed at our comprehensive stroke center from June 2020 to May 2022 to identify AIS patients with cocaine‐positive urine toxicology screens on admission. Baseline demographics, urine toxicology, National Institute of Health Stroke Scale (NIHSS) scores, neuroimaging, Trial of ORG 10127 in Acute Stroke Treatment (TOAST) criteria, location of stroke, home medications, comorbidities, medical management, and outcomes including modified Rankin Score (mRS) were reported. Results A total of 74 AIS patients were identified to be cocaine‐positive. Of these patients, 14 underwent endovascular thrombectomy (EVT). Only 3 of these 14 patients received intravenous thrombolytics. Including the EVT group, 8 out of 74 AIS patients received thrombolytics. The mean age was found to be 61 years with 86% being male. The most common locations of large vessel occlusion were the M2 branch of the right middle cerebral artery (MCA) (40%), the M2 branch of the left MCA (33%), the M1 branch of the right MCA (13%), left internal carotid artery (7%), and A1 branch of the anterior cerebral artery (7%). Based on TOAST criteria, 64% of strokes were large artery atherosclerosis, 29% cardioembolic, and 7% cryptogenic stroke. The mean initial NIHSS was 14. Average mRS on admission was found to be < 1 and follow‐up mRS at 3 months was found to be 3. Conclusion Our data suggest that cocaine patients who underwent EVT on average had unfavorable functional outcomes defined as mRS > 2, on follow‐up mRS at 3 months. This study highlights the importance of future larger studies to investigate endovascular thrombectomy +/‐ thrombolytics in cocaine‐related AIS.